Security Coproduction and Organized Crime: Micro Dynamics and Risk Factors in Guadalajara, Mexico - Strickland, Rebecca Danielle (Crime & delinquency, 2025)
This research questions the relevance of the collective efficacy, citizen security, and broken windows theories in a Guadalajara neighborhood dominated by organized crime. Risk factors and perceptions of security were explored through observation, surveys, focus groups, collective mapping, and interviews with residents, police, and the coordinators of projects to coproduce security. Class barriers, the neighborhood’s layout, and fear provoked by the plaza that controls the local drug trade were identified as conditions that facilitate crime. However, isolated actions to coproduce security were also detected. Findings lead to reflections on how leading crime prevention theories should be adapted in such contexts, as well as the risks involved in coproducing and researching security in areas controlled by organized crime groups.